Efek Mediasi dari Kepuasan Kerja pada Hubungan antara Learning Organization dan Kinerja Karyawan - Ummi Sarah; Adolf Bastian; Ririn Handayani (CV. ITTC INDONESIA, 2026)
This study aims to examine the mediating role of job satisfaction in the relationship between learning organization and employee performance at the Regional Financial and Asset Management Agency (BPKAD) of Dumai City. This research employed a quantitative approach using a survey method. The population consisted of 83 employees, all of whom were selected as the sample using a saturated sampling technique. Data were collected through questionnaires utilizing a 5-point Likert scale. The data were analyzed using Structural Equation Modeling (SEM) with SmartPLS 3.0 software. The results indicate that: (1) learning organization has a positive and significant effect on job satisfaction; (2) job satisfaction has a positive and significant effect on employee performance; (3) learning organization has a positive and significant effect on employee performance; and (4) job satisfaction significantly mediates the effect of learning organization on employee performance. These findings contribute to the theoretical development of learning organization concepts and offer practical implications for human resource management in the public sector.